SYSTEM ARTIFICIAL INTELEGENCE DALAM MENDIAGNOSA AWAL CONSTIPATION DISEASE (SEMBELIT) - Egi Affandi; Trinanda Syahputra; Ahmad Fitri Boy; Lusiyanti Lusiyanti (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2022)
Abstract: Expert System is a part of artificial intelligence that imitates human reasoning. Utilization of technology makes it easier for humans to access information without being limited by space and time. With the construction of an Artificial Intelligence System for Early Diagnosing Constipation Disease Using the Dempster Shafer Method, it is hoped that it will make it easier for the public to consult about constipation disease. So that the community can take early action to overcome the problem of constipation disease (constipation). The stages in this research are collecting data to several experts, identifying the data as the basic rule of constipation disease, then developing the system, then testing the system and implementing the system. This study uses a system that can provide additional knowledge to the general public, especially about constipation disease. This application developed aims to help provide clear information for the general public, is expected to help in handling constipation disease (constipation) and provide the right solution, by only paying attention to the symptoms experienced.Keywords: Expert System; constipation disease; Dempster Shafer; Website.Abstrak: Sistem Pakar merupakan bagian dari kecerdasan buatan yang meniru penalaran manusia. Pemanfaatan teknologi memudahkan manusia untuk mengakses informasi tanpa terbatas ruang dan waktu. Dengan dibangunnya System Artificial intelegence dalam Mendiagnosa awal constipation disease (Sembelit) Menggunakan Metode Dempster Shafer diharapkan akan memudahkan masya-rakat untuk berkonsultasi tentang constipation disease. Sehingga masya-rakat dapat melakukan tindakan awal untuk mengatasi masalah constipation disease (sembelit). Tahapan dalam penelitian ini adalah pengumpulan data kepada beberapa orang pakar, identifikasi data sebagai Rule dasar constipation disease kemudian melakukan pembangunan sistem, selanjutnya dilakukan pengujian sistem dan implementasi sistem. Pada penelitian ini menggunakan sistem yang dapat memberikan tambahan pengetahuan kepada masyarakat umum, khususnya tentang constipation disease. Aplikasi yang dikembangkan ini bertujuan untuk membantu memberikan informasi yang jelas bagi masyarakat umum, diharapkan dapat membantu dalam penanganan constipation disease (Sembelit) memberikan solusi yang tepat, dengan hanya memperhatikan gejala- gejala yang dialami.Kata kunci: Expert System; constipation disease; Dempster Shafer; Website.